2016
DOI: 10.1139/er-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal detoxification and tolerance mechanisms in plants: Implications for phytoremediation

Abstract: 30Heavy metals such as cobalt, copper, manganese, molybdenum, and zinc are essential in trace 31 amounts for growth by plants and other living organisms. However, in excessive amounts these 32 heavy metals have deleterious effects. Like other organisms, plants possess a variety of 33 detoxification mechanisms to counter the harmful effects of heavy metals. These include, the 34 restriction of heavy metals by mycorrhizal association, binding with plant cell wall and root 35 excretions, metal efflux from the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(57 citation statements)
references
References 185 publications
2
54
1
Order By: Relevance
“…During the present study, higher contents of Cd were observed in roots as compared to aerial parts of C. longifolius plants under Cd stress. The cadmium may be absorbed in roots through symplastic or apoplastic pathways [52]. Similar to our findings, higher Cd contents were observed in roots of tall fescue and bluegrass plants subjected to Cd stress [53].…”
Section: Effect Of Bacterial Inoculation On Physiological Traits Of Csupporting
confidence: 88%
“…During the present study, higher contents of Cd were observed in roots as compared to aerial parts of C. longifolius plants under Cd stress. The cadmium may be absorbed in roots through symplastic or apoplastic pathways [52]. Similar to our findings, higher Cd contents were observed in roots of tall fescue and bluegrass plants subjected to Cd stress [53].…”
Section: Effect Of Bacterial Inoculation On Physiological Traits Of Csupporting
confidence: 88%
“…Conversely, increasing the pH causes immobilization by formation of insoluble compounds or increased anion exchange capacity (Gleyzes et al, 2002). The pH variations therefore have complex and sometimes opposite consequences on the mobility of heavy metals, particularly in the presence of organic and inorganic ligands (Kushwaha et al, 2016). It is a fundamental element in controlled nutrition, because it determines assimilation conditions of mineral elements.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Bamboo stakes are used to prevent laterite from aglomerating due to sulfuric acid leach. Bamboo can be planted around the industrial area and can be used as a phytoremediation plant [13]. In general heap leaching using PVC plastic instead of bamboo that is difficult to degrade.…”
Section: Resultsmentioning
confidence: 99%